Undifferentiated connective tissue dysplasia as a predictor of heart rate disorders in combination with gastroesophageal reflux disease in children - Herasymova, Oksana; Filonova, Tetiana (ScienceRise: Medical Science, 2021)
The aim: to improve the early diagnosis of arrhythmia in combination with gastroesophageal reflux disease (GERD) in children, by studying the risk of connective tissue dysplasia on the occurrence of this pathology. Materials and methods. We examined 100 children aged 8 to 18 years, mean age 13.7±2.7 years, of which 32 children with arrhythmias without combined pathology were group I, 36 children with concomitant GERD - group II and 32 children with GERD without concomitant arrhythmias - group III. Patients underwent clinical and instrumental studies (electrocardiography, Holter daily ECG monitoring, esophagogastroduodenoscopy and pH-metry) and evaluation of phenotypic signs of NDST according to the criteria of T. Milkovskaya-Dimitrova and A. Karkasho. Results. A risk factor for the formation of combined pathology in children in the form of arrhythmia and GERD was identified, namely the next main phenotypic feature of NDST (undifferentiated connective tissue dysplasia) – dysplastic tooth growth. Also, predictors of both an isolated variant of arrhythmia in children and arrhythmia in combination with GERD – high height and scoliotic posture were identified. In this case, the risk factor for an isolated variant of arrhythmia in children, according to the results of the study is asthenic constitution. The severity of NDST in the studied groups was determined. The analysis of the results revealed the absence of a statistically significant relationship between the severity of NDST and study groups, although it should be noted that in children of group III the first degree of NDST was not observed in general. Conclusions. It was found that asthenic constitution, dysplastic tooth growth, tall stature and scoliotic posture are statistically significant risk factors for the development of the studied pathologies. There were no statistically significant differences between the study groups regarding the severity of NDST, but there was a complete lack of detection in children of group III (children with isolated GERD without concomitant arrhythmia) of the first degree of NDST